Andragogi: Pendekatan untuk Meningkatkan Pengetahuan Dan Kemahiran Di Kalangan Operator Inap Desa Malaysia (Sains Humanika, 2018)
Homestay, as a community-based tourism product of Malaysia has increased in popularity and demand among domestic and international tourists. Given that most of these operators comprised of adults who do not possess any background in the tourism industry, hence various forms of training should be emphasised in order to raise their quality of skills and hospitality. In line with the above qualitative approach was adopted to identify the extent to which a particular adult’s education (andragogy) is capable of increasing him/her knowledge in ensuring the success in the homestay programme. A study involving 5 homestays in Johor had produced 3 themes that discuss the needs of knowledge and skills of homestay operators which consisted of adults aged 40 years old and above.
Keywords: Homestay; adults; andragogy